Output Swarm Stability and Stabilization for High‐Order Linear Swarm Systems. Issue 1 (27th October 2014) - Xi, Jianxiang; Liu, Hao; Yu, Zhiyong; Yang, Bailong; Liu, Guangbin
Abstract: Output swarm stability and stabilization problems for high‐order linear swarm systems with directed interaction topologies are investigated. First, sufficient conditions for output swarm stability are presented, and an approach is proposed to determine the absolute output motion, where the influences of initial states of agents and swarm stabilizing protocols are given. Moreover, it is shown that swarm systems with the same initial states but different balanced interaction topologies have the same absolute output motion. Then, sufficient conditions for output swarm stabilization, which are independent of the number of agents, are presented. Finally, numerical simulations are shown to illustrate the correctness of theoretical results.